Molecular prevalence of Coenurus cerebralis in sheep exhibiting neurological symptoms in Kazakhstan - Kozhayeva, Aigerim; Kereyev, Abzal; Shevtsov, Alexandr; Abdigulov, Bolat; Smagulov, Darkhan; Khamzina, Saltanat; Kulzhanova, Botagoz; Nurzhanova, Kulsara; Bupebayeva, Lyaila; Khamzina, Aigerim (Frontiers in Veterinary Science, 2025)
Coenurosis, caused by the larval stage of Taenia multiceps — Coenurus cerebralis, is a severe parasitic disease that affects the central nervous system of sheep and causes significant economic losses in livestock farming. This study aimed to determine the molecular prevalence of Coenurus cerebralis in sheep with neurological symptoms in Kazakhstan using conventional PCR followed by Sanger sequencing. The study was conducted in the West Kazakhstan and Abay regions. However, insufficient data from other regions limits the development of effective national control measures. Of the 100 sheep examined, clinical signs of the disease were detected in 15 animals. During molecular analysis of the mitochondrial genes COX1 and NAD1, positive results were obtained in 9 samples (81%). The data obtained confirm the high diagnostic value of PCR and the effectiveness of mitochondrial markers for identifying C. cerebralis. The results contribute to a better understanding of the epidemiology and pathogenesis of cenurosis and can be used to develop effective strategies for the prevention and control of the disease in regions with developed sheep farming. Kazakhstani isolates are grouped within a single haplotype (Hap47), which belongs to a major, widely distributed lineage. This suggests potential links with other countries and may reflect historical migration patterns or species dispersal routes. Isolates from Italy, Turkey, and Iran also show a strong association with the principal haplotype lineages, indicating a shared genetic background.